The Effect of Training and Motivation on Employee Performance at PT Astra Graphia Tbk. Makassar Branch - Khairinnisai K, Syarifah; Ruma, Zainal; Akbar, Abdi; Sahabuddin, Romansyah; Amalia Hamka, Rezky (International Humanity Advance, Business & Sciences, 2024)
The study examines the impact of training and motivation on the performance of employees at PT. Astra Graphia Tbk Makassar Branch. The aim of this study is to find out the impact of training and motivation on the performance of employees at PT. Astra Graphia Tbk Makassar Branch. The population in this study is a total of 34 employees. The sample of this study is an entire member of the population of 34 people with this type of quantitative research. The data collection technique is done by scattering the questionnaire. The data analysis technique used is double linear regression analysis using Statistical Product Servive Solution. (SPSS). The results of the research show that: 1) there is a positive and significant influence on the training on the performance of employees at PT. Astra Graphia Tbk branch of Makassar; 2) there is a significant and positive influence of the motivation on the employee performance at PT. Astra Graphia Tbk branch of Makassar; and 3) There is positive and important influence simultaneously of the training and motivation of employees on performance at an PT. Astra Graphia Tbk branch of Makassar.